0.2(x+1)=0.3(x+11)

Simple and best practice solution for 0.2(x+1)=0.3(x+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.2(x+1)=0.3(x+11) equation:


Simplifying
0.2(x + 1) = 0.3(x + 11)

Reorder the terms:
0.2(1 + x) = 0.3(x + 11)
(1 * 0.2 + x * 0.2) = 0.3(x + 11)
(0.2 + 0.2x) = 0.3(x + 11)

Reorder the terms:
0.2 + 0.2x = 0.3(11 + x)
0.2 + 0.2x = (11 * 0.3 + x * 0.3)
0.2 + 0.2x = (3.3 + 0.3x)

Solving
0.2 + 0.2x = 3.3 + 0.3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.3x' to each side of the equation.
0.2 + 0.2x + -0.3x = 3.3 + 0.3x + -0.3x

Combine like terms: 0.2x + -0.3x = -0.1x
0.2 + -0.1x = 3.3 + 0.3x + -0.3x

Combine like terms: 0.3x + -0.3x = 0.0
0.2 + -0.1x = 3.3 + 0.0
0.2 + -0.1x = 3.3

Add '-0.2' to each side of the equation.
0.2 + -0.2 + -0.1x = 3.3 + -0.2

Combine like terms: 0.2 + -0.2 = 0.0
0.0 + -0.1x = 3.3 + -0.2
-0.1x = 3.3 + -0.2

Combine like terms: 3.3 + -0.2 = 3.1
-0.1x = 3.1

Divide each side by '-0.1'.
x = -31

Simplifying
x = -31

See similar equations:

| -6(x+1)+2(7x+9)= | | 2x+149=9x-5 | | 9-4(y+7)=7+3y | | x^4+9x^2+400=0 | | 3b-2=19 | | 2x-3+5x=4+4x+1 | | 2x+y-2z=2 | | s^2+9s+81=0 | | 7*6= | | 89-7x=29x+21 | | X^3=81x | | x-4y+2z=-11 | | 26=7x+x+2 | | 30-5a=10 | | -.5(y+5)=-1 | | c/8+10=15 | | 3x+2y-4z=3 | | c/8=15 | | 12x^2+12x-24=0 | | 12-10x=62-24x | | -7(x+1)=2x-34 | | 24a-22=-4(1-6n) | | -x+3=-3x+11 | | 4x^2-48+44=0 | | x^2+36x=144 | | 6x-3=2x+5 | | 9x(3x)2x= | | 8x+9+2(10+x)=2x+29 | | 0.4x-0.6x-5=1 | | x=35 | | x^2+36x-144=0 | | -.33m-7=5 |

Equations solver categories